2015
DOI: 10.1371/journal.pone.0119630
|View full text |Cite
|
Sign up to set email alerts
|

Fall Risk Awareness and Safety Precautions Taken by Older Community-Dwelling Women and Men—A Qualitative Study Using Focus Group Discussions

Abstract: IntroductionDaily life requires frequent estimations of the risk of falling and the ability to avoid a fall. The objective of this study was to explore older women’s and men’s understanding of fall risk and their experiences with safety precautions taken to prevent falls.MethodsA qualitative study with focus group discussions was conducted. Eighteen community-dwelling people [10 women and 8 men] with and without a history of falls were purposively recruited. Participants were divided into two groups, and each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
31
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 38 publications
10
31
0
6
Order By: Relevance
“…Older adult women were more likely to fall than older adult men (19) . The fear of falling among older adult women was associated with reduced physical activity (19) ; obesity (20)(21) ; impairment of activities of daily living (ADLs) (19) ; social isolation (4) ; higher depressive symptoms (20,22) ; higher probability of future falls (23) . The fear of falling among older adult women is influenced by a number of factors peculiar to gender, such as a higher prevalence of chronic non-communicable diseases (NCDs) and musculoskeletal frailty (23) ; low bone density after menopause and greater and more rapid loss of muscle mass, due to the hormonal decrease (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Older adult women were more likely to fall than older adult men (19) . The fear of falling among older adult women was associated with reduced physical activity (19) ; obesity (20)(21) ; impairment of activities of daily living (ADLs) (19) ; social isolation (4) ; higher depressive symptoms (20,22) ; higher probability of future falls (23) . The fear of falling among older adult women is influenced by a number of factors peculiar to gender, such as a higher prevalence of chronic non-communicable diseases (NCDs) and musculoskeletal frailty (23) ; low bone density after menopause and greater and more rapid loss of muscle mass, due to the hormonal decrease (24) .…”
Section: Discussionmentioning
confidence: 99%
“…We understand that this type of education for older people is aimed at broadening their awareness of this issue so that they can take actions through looking after themselves. As was frequently observed, older people with greater awareness of the issue opted to modify their dwellings to reduce domestic 17 risks. Many of these modifications were easily identifiable and remediable.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that only the variable of "age" was a sociodemographic determinant for the presence of household risk factors. This suggested that amongst those that are older, the preventative habits are established based on prior experiences of falls 17 . Considering that individuals with a greater understanding of these issues presented a lower presence of household risk factors, this fact infers that the actual situation can be changed with the implementation of reading strategies on health and healthy life style habits that are universally objective when dealing with the prevention of falls 8,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3,4) Various studies have reported that the precautions the elderly took to prevent falls included asking for assistance when inserting light bulbs, avoiding risky behaviors, moving slowly and using equipment to support their walking. (13)(14)(15) Stevens, Noonan and Rubenstein (2010) recommended that fall prevention programs be evaluated in order to improve fall prevention behaviors among the elderly. (16) The most frequently displayed fall prevention behavior among the elderly are exercise, vitamin D supplementation, environmental modification, education, and multi-factorial programs.…”
Section: Introductionmentioning
confidence: 99%